ANALISIS SUBJUNKTOR WENN DALAM ROMAN ZELTEN MIT MEERSCHWEIN KARYA MAREIKE KRÜGEL - Iin Fatimah Trihandayani, - (2022)
ABSTRAKSI Trihandayani, Iin Fatimah. 2022. Analisis Subjunktor wenn dalam Roman Zelten mit Meerschwein Karya Mareike Krügel. Skripsi Program Studi Pendidikan Bahasa Jerman. Fakultas Pendidikan Bahasa dan Sastra. Universitas Pendidikan Indonesia. Subjunktor wenn merupakan salah satu jenis kata penghubung dalam bahasa Jerman yang membentuk Nebensatz yaitu letak verba yang dikonjugasi berada di akhir kalimat. Kalimat yang menggunakan Subjunktor wenn dapat dimaknai secara temporal 'menunjukkan adanya hubungan waktu' dan kondisional 'menunjukkan sebuah syarat'. Dalam memahami kedua jenis makna tersebut terkadang pemelajar masih mengalami kesulitan. Pada penelitian ini Subjunktor wenn yang dianalisis berasal dari sumber data berupa roman yang berjudul Zelten mit Meerschwein karya Mareike Krügel. Tujuan penelitian ini adalah: 1) Untuk mengetahui kalimat apa saja yang menggunakan Subjunktor wenn dalam sumber data. 2) Untuk mengetahui dan memahami jenis-jenis Subjunktor wenn dalam sumber data. Penelitian ini menggunakan teori Helbig & Buscha (2001) untuk mengetahui kalimat yang menggunakan Subjunktor wenn dan mengklasifikasikan jenisnya. Metode yang digunakan dalam penelitian ini yaitu metode deskriptif kualitatif. Hasil penelitian menunjukkan bahwa: 1) Kalimat yang menggunakan Subjunktor wenn dalam sumber data berjumlah 111 kalimat. 2) Jenis Subjunktor wenn yang ditemukan dalam sumber data dikelompokkan menjadi dua, yaitu temporale Subjunktor 'subjungsi temporal' dan konditionale Subjunktor 'subjungsi kondisional'. Hasil analisis menunjukkan bahwa Subjunktor wenn sebagai subjungsi kondisional lebih banyak muncul yaitu berjumlah 71 kalimat dibandingkan dengan Subjunktor wenn sebagai subjungsi temporal yang berjunlah 40 kalimat. Jenis-jenis Subjunktor wenn ini dapat menjadi pengetahuan tambahan bagi pemelajar untuk memahami makna kalimat yang menggunakan Subjunktor wenn. Kata kunci: subjungsi, subjungsi kondisional, subjungsi temporal, subjungsi wenn ABSTRACT Trihandayani, Iin Fatimah. 2022. An Analysis of Subjunktor wenn in Roman Zelten mit Meerschwein by Mareike Krügel. Bandung. A Thesis at the Departement of German Education. Faculty of Language and Literatur Education. Indonesian University of Education. The "Subjunktor wenn" is a type of conjunction in German that forms Nebensatz, which is to put the conjugated verb at the end of sentence. Sentences that use the subjunktor wenn can be interpreted temporally as 'showing a time' and as conditionally 'showing a condition'. In understanding the two types of meaning, sometimes students still have difficulty. In this research, "Subjunktor wenn" will be analyzed in "Roman Zelten mit Meerschwein" by Mareike Krügel. The purposes of this research are to find out: 1) What kind of sentences that use "Subjunktor wenn" in the data source. 2) and understanding the types of "Subjunktor wenn" in the data source. This reasersch uses the theory of Helbig & Buscha (2001) to find out sentences that use the "Subjunktor wenn" and classify their types. The method used in this reasersch is a qualitative descriptive method. The reasersch's results are: 1) There are 111 sentences that use the "Subjunktor wenn" in the data source. 2) The types of "Subjunktor wenn" classified into two, they are "temporale Subjunktor" and "konditionale Subjunktor". The results of the analysis show that the subjunktor wenn as a "konditionale Subjunktor" appears more, amounting to 71 sentences, compared to the subjunktor wenn as a "temporale Subjunktor" which amounts to 40 sentences. These types of "Subjunktor wenn" can be additional knowledge for students to understand the meaning of sentences using "Subjunktor wenn". Keywords: konditionale Subjunktor, Subjunktor, Subjunktor wenn, temporale subjunktor